A Preliminary Adaptation and Validation of the Indonesian Version of the Loneliness and Aloneness Scale for Children and Adolescent (LACA) - Gultom, Lydia Agnes; Triwahyuni, Airin; Qodariah, Laila (Faculty of Psychology, Universitas Gadjah Mada, 2024)
Measuring loneliness in children and adolescents is crucial, as it is a prevalent issue that can impact their emotional and social development. Despite its importance, there are limited validated tools available to assess loneliness within the Indonesian cultural context. The Loneliness and Aloneness Scale for Children and Adolescents (LACA) is a widely used instrument for assessing feelings of loneliness and aloneness among children and adolescents. This study aimed to adapt and collect evidence of the validity of the Indonesian version of the LACA following the International Test Commission (ITC) Guidelines for Translating and Adapting Tests. Using the convenience sampling technique, 297 children and adolescents aged 10–18 years were selected as respondents in this study. The results show that the Indonesian version of four LACA sub-scales has good internal consistency. Confirmatory factor analysis shows that the four-factor model has an acceptable model fit. However, six items were omitted from the LACA loneliness measurement model for having a low contribution to loneliness. As a result, the four-factor model with fewer items shows a better fit. According to the research findings, the Indonesian version of the LACA can be used to measure loneliness and attitudes toward aloneness in the population of children and adolescents in Indonesia, with a recommendation to omit six items. The results of the tests on alternative two-factor models show that the loneliness in relationships with parents and loneliness in relationships with peers sub-scales can be used separately to measure the source of loneliness in children and adolescents in Indonesia.